Protection against internal and external hazards in the operation of nuclear power plants : specific safety guide. (Safety standards series ;, 2022)
"This Safety Guide provides specific recommendations on protection against internal and external hazards in the operation of nuclear power plants. It provides new or updated recommendations derived from enhanced understanding of operational aspects of hazards and combinations of hazards. Operating experience gained from incidents and accidents in nuclear power plants around the world has demonstrated that fire can be an important risk contributor in many Member States. However, there are other internal and external hazards that have also to be considered in the design and operation of nuclear power plants. This Safety Guide supersedes and expands the scope of lAEA Safety Standards Series No. NS- G-2. 1, Fire Safety in the Operation of Nuclear Power Plants, to include recommendations on these other hazards."--Publisher's description.